Innovación gastronómica: desarrollo de tres postres utilizando harina de haba como ingrediente principal - Cadena Guagua, Nixon Israel (2024)
In the context of Ecuadorian gastronomy, bean flour, rich in protein and gluten-free, represents an ingredient with great nutritional potential. However, its use is limited in the kitchen, particularly in confectionery, which presents an opportunity to innovate and diversify the culinary offer. The general objective of this integrative project was to develop three dessert recipes using fava bean flour through innovative culinary techniques and substitution of conventional ingredients. The specific objectives included: conducting a bibliographic research on the nutritional properties of fava bean flour and its application in desserts, developing three innovative recipes using fava flour as the main ingredient, and evaluating the acceptance of these desserts through a sensory tasting. The methodology combined a comprehensive literature review on fava bean flour with practical recipe development. Sensory tastings were conducted with expert culinary participants, who evaluated the taste, texture, aroma, sweetness, color, and presentation of the desserts. The expected results of this study include the creation of new dessert options that integrate fava bean flour, increasing its visibility and acceptance in Ecuadorian gastronomy. It is expected that this research will promote a more diverse and healthy diet, highlighting the versatility and nutritional benefits of fava bean flour in the daily diet.In the context of Ecuadorian gastronomy, bean flour, rich in protein and gluten-free, represents an ingredient with great nutritional potential. However, its use is limited in the kitchen, particularly in confectionery, which presents an opportunity to innovate and diversify the culinary offer. The general objective of this integrative project was to develop three dessert recipes using fava bean flour through innovative culinary techniques and substitution of conventional ingredients. The specific objectives included: conducting a bibliographic research on the nutritional properties of fava bean flour and its application in desserts, developing three innovative recipes using fava flour as the main ingredient, and evaluating the acceptance of these desserts through a sensory tasting. The methodology combined a comprehensive literature review on fava bean flour with practical recipe development. Sensory tastings were conducted with expert culinary participants, who evaluated the taste, texture, aroma, sweetness, color, and presentation of the desserts. The expected results of this study include the creation of new dessert options that integrate fava bean flour, increasing its visibility and acceptance in Ecuadorian gastronomy. It is expected that this research will promote a more diverse and healthy diet, highlighting the versatility and nutritional benefits of fava bean flour in the daily diet.